Impact of delayed cord clamping on mesenchymal, hemopoietic progenitor, and immune cells in very preterm neonates - Drogouti, Eftychia; Rallis, Dimitrios; Fleva, Alexandra; Giannakou, Anastasia; Lithoxopoulou, Maria; Kavga, Maria; Mikos, Themistoklis; Soubasi, Vasiliki; Diamanti, Elisavet; Roilides, Emmanuel; Tsakalidis, Christos (Frontiers in Pediatrics, 2025)
ObjectiveWe aimed to investigate the impact of delayed cord clamping (DCC) on the levels of blood mesenchymal (MSCs), hemopoietic progenitor (HPCs), and immune cells in very preterm neonates.MethodsWe prospectively examined 21 neonates with a median gestational age of 32 weeks (interquartile range, IQR 29–32) who had DCC, and 19 neonates with a median gestational age of 31 weeks (IQR 30–32) who had immediate cord clamping (ICC). We measured the levels of MSCs, HPCs, very small embryonic-like stem cells (VSELs), early endothelial progenitor cells (EPCs), late EPCs, and the immunophenotype in the first, 10th, and 30th day of life, and associated them with late-onset sepsis and bronchopulmonary dysplasia (BPD).ResultsDCC-neonates compared to ICC-neonates had significantly higher values of MSCs (846 vs. 316 cells per million cytometric events, p = 0.003), HPCs (191 vs. 115 cells per million cytometric events, p = 0.034), and lower values of VSELs (21 vs. 37 cells per million cytometric events, p = 0.044) and late EPCs (7 vs. 19 cells per million cytometric events, p = 0.017) at birth. Neonates with late-onset sepsis, in comparison to neonates with no sepsis, had significantly higher values of early (20 vs. 0.3 cells per million cytometric events, p = 0.011) and late EPCs (32 vs. 8 cells per million cytometric events, p = 0.033). In addition, neonates with BPD had significantly higher values of late EPCs compared to neonates without BPD (27 vs. 8 cells per million cytometric events, p = 0.041). DCC, adjusted for gestational age and birth weight, was significantly associated with higher levels of MSCs, HPCs, and lower levels of VSELs and late EPCs.ConclusionsIn very preterm neonates with DCC, MSCs and HPCs are higher, while VSELs and late EPCs are lower in the umbilical cord blood, compared to neonates with ICC. Early and late EPCs were associated with late-onset sepsis and BPD. Further studies are warranted to explore the association of these findings with the long-term clinical outcomes.